SARS-CoV-2 Risk Management in Clinical Psychiatry: A Few Considerations on How to Deal With an Unrivaled Threat - Kreuzer, Peter M.; Baghai, Thomas C.; Rupprecht, Rainer; Wittmann, Markus; Steffling, Dagmar; Ziereis, Michael; Zowe, Marc; Hausner, Helmut; Langguth, Berthold (Frontiers in Psychiatry, 2020)
The pandemic spread of the corona virus SARS-CoV-2 has even-handedly shattered national and international health systems and economies almost in an instant. As numbers of infections and COVID-19-related deaths rise from day to day, fears and uncertainties on how to deal with this unknown threat are extremely present both for individuals and societies as a whole. In this manuscript we aim to exemplarily describe the bullet points concerning (a) the internal risk management, (b) the organizational and structural changes and (c) the communicational strategies applied in a Psychiatric University Hospital in the South-ern part of Germany. The authors are well aware about the fact that almost none of these considerations may be considered as evidence-based at the moment. However, the authors trust that these reflections and experiences may be useful as an orientation for similar risk con-stellations in other afflicted countries due to the temporal delay of the pandemic course.